(untitled) (Research, Society and Development, 2025)
Mandibular angle fractures are among the most frequent injuries of the maxillofacial skeleton and carry a high risk of functional and aesthetic complications. This study aimed to report a clinical case of left mandibular angle fracture, highlighting diagnostic strategies, surgical access selection and fixation system, and to critically review fixation techniques described in the literature. An exploratory, descriptive, qualitative case report was conducted in a 42-year-old male patient who sustained facial trauma during physical aggression, presenting severe pain, malocclusion, and limited mouth opening. Diagnosis was established through thorough clinical examination and cone-beam computed tomography, including three-dimensional reconstruction for surgical planning. Open reduction was performed via intraoral approach with rigid internal fixation using two monocortical miniplates, following well-established biomechanical principles. The postoperative period evolved uneventfully, with satisfactory occlusal restoration and facial symmetry. Literature analysis shows a progressive evolution of fixation methods, from traditional wire fixation and maxillomandibular immobilization to plates and screws, including miniplates, 3D plates and locking plates, as well as advances in imaging and artificial intelligence for fracture detection. Individualized selection of surgical access and fixation system, supported by accurate imaging diagnosis, is decisive to achieve functional and aesthetic success in the management of mandibular angle fractures.